2020
DOI: 10.1111/acel.13192
|View full text |Cite
|
Sign up to set email alerts
|

The aged hematopoietic system promotes hippocampal‐dependent cognitive decline

Abstract: Exposure to the aging systemic milieu, through models such as heterochronic parabiosis, promotes cellular, molecular, and structural changes in the brain that lead to cognitive decline (Katsimpardi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Exposure to a young circulatory system rejuvenates muscle regenerative capacity by activating satellite cells and restores the proliferative capacity of hepatic progenitors (42). Heterochronic parabiosis also affects neurogenesis and associated learning and memory, improving these capacities in old mice (43,58,59), while impairing them in young mice (60)(61)(62). CyPA (61) and chemokines including CCL11 (62) have been identified as negative regulators, while TIMP2 (58) and GPLD1 (59) were identified as positive regulators of these functions.…”
Section: Extracellular Vesicles As a Critical Regulatory Component For Mammalian Aging And Longevitymentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to a young circulatory system rejuvenates muscle regenerative capacity by activating satellite cells and restores the proliferative capacity of hepatic progenitors (42). Heterochronic parabiosis also affects neurogenesis and associated learning and memory, improving these capacities in old mice (43,58,59), while impairing them in young mice (60)(61)(62). CyPA (61) and chemokines including CCL11 (62) have been identified as negative regulators, while TIMP2 (58) and GPLD1 (59) were identified as positive regulators of these functions.…”
Section: Extracellular Vesicles As a Critical Regulatory Component For Mammalian Aging And Longevitymentioning
confidence: 99%
“…42 Heterochronic parabiosis also affects neurogenesis and associated learning and memory, improving these capacities in old mice, 43,58,59 while impairing them in young mice. [60][61][62] CyPA 61 and chemokines including CCL11 62 have been identified as negative regulators, while TIMP2 58 and GPLD1 59 were identified as positive regulators of these functions. Outside of parabiosis, studies have demonstrated that plasma extracted from exercised animals confers antiaging cognitive benefits 59 and that there are substantial changes to the plasma EV pool, including increased numbers of EVs during exercise in humans.…”
Section: Blood-based Antiaging Therapiesmentioning
confidence: 99%
“…Previously, heterochronic transplantation of marrow or HSCs in mice has been shown to affect (modulate) a variety of phenotypes 1518 . Most recently, aged HSCs were found to induce circulating cyclophilin A, encoded by Ppia 19 , a gene ranked among the top differentially expressed across cell types exposed to aged blood (Extended Data Fig. 5).…”
Section: Cell Type-specific Differential Gene Expressionmentioning
confidence: 99%
“…During aging there is an increase in the blood circulation of IL-6 and TNF-α, which also corresponds to a higher expression of these factors in the choroid plexus (CP) (Smith et al, 2018). Likewise, heterochronic reconstitution experiments have also recently indicated that old hematopoietic cells reduce hippocampal neurogenesis through increased levels of cyclophilin A, a SASP factor (Smith et al, 2020). Together, these changes may account for the accumulation of pro-aging SASP factors in the old blood, which are also likely to promote senescence induction at the vascular level, ultimately contributing to the deterioration of adult neurogenesis.…”
Section: The Aging Systemic Milieu: Blood-borne Effects On Neurogenesismentioning
confidence: 99%